Volterra transfer functions in analysis of the stochastic filter driven by harmonic plus gaussian noise input - Kharchenko, O.I.; Kartashov, V.M. (Radiotekhnika, 2019)
The work is a continuation of the cycle of studies of nonlinear systems at various input effects. Previously, cases of harmonic input signal, white Gaussian noise were considered. In present paper a stochastic filtering of the minimum shift keying waveform is considered. The equation of a stochastic resonance is solved by means of Volterra series in case of harmonics plus Gaussian noise input. The solution is based on Volterra transfer functions.